2020
DOI: 10.1007/s00246-020-02436-6
|View full text |Cite
|
Sign up to set email alerts
|

The Cardiovascular Stress Response as Early Life Marker of Cardiovascular Health: Applications in Population-Based Pediatric Studies—A Narrative Review

Abstract: Stress inducement by physical exercise requires major cardiovascular adaptations in both adults and children to maintain an adequate perfusion of the body. As physical exercise causes a stress situation for the cardiovascular system, cardiovascular exercise stress tests are widely used in clinical practice to reveal subtle cardiovascular pathology in adult and childhood populations with cardiac and cardiovascular diseases. Recently, evidence from small studies suggests that the cardiovascular stress response c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 106 publications
0
5
0
Order By: Relevance
“…However, combined with CMR, cycling cannot be combined with long breath holds and a treadmill exercise is not feasible within the MRI. Isometric handgrip exercise is the most feasible physical stressor in combination with CMR as it allows scanning without losing image quality due to movement artefacts [ 19 ]. This is the first large pediatric population-based cohort study exploring the cardiovascular effects of an isometric handgrip exercise combined with detailed cardiovascular measurements [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, combined with CMR, cycling cannot be combined with long breath holds and a treadmill exercise is not feasible within the MRI. Isometric handgrip exercise is the most feasible physical stressor in combination with CMR as it allows scanning without losing image quality due to movement artefacts [ 19 ]. This is the first large pediatric population-based cohort study exploring the cardiovascular effects of an isometric handgrip exercise combined with detailed cardiovascular measurements [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…To provoke a cardiovascular stress reaction, we used a sustained isometric handgrip exercise. Earlier studies have shown that a sustained handgrip of 30% to 40% of the maximal voluntary contraction (MVC) for 7 min is a feasible exercise that leads to a substantial increase in heart rate and blood pressure [ 19 ]. To measure the MVC, all participants were tested in the seated position with their elbow flexed at 90°.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Children 2022, 9, 654 2 of 13 originate in childhood [6]. Throughout the maturation process (i.e., from babyhood to adulthood), some variations in the modulation of the autonomic nervous system over the heart occur, inducing changes in heartbeat patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Heart rate (HR) can be used to detect differences in cardiovascular health in preschool children by measuring the cardiovascular response to physical exercise with an uncomplicated clinical assessment [6]. Therefore, HR is a biomarker that can be utilized to determine physiological function and health status.…”
Section: Introductionmentioning
confidence: 99%